State Diagram, Sorption Isotherm and Color of Blueberries as a Function of Water Content - Matiacevich, S (Elsevier B.V., 2013)
A state diagram of blueberries was developed using freezing and glass transition curves, and maximal-freeze-concentration condition in order to predict the behavior and physical changes of fresh andlyophilized blueberries. Freezing points (Clausius-Clapeyron equation) and glass transition temperature (Gordon-Taylor equation) were measured by differential scanning calorimetry (DSC). Color samples weremeasured by computer vision system. Isotherms data was fitted using GAB, Peleg and Iglesias-Chirife equations. Glass transition decreased as decreasing solids content due to water plasticizing effect. Lyophilized andfresh samples varied their color; however thermal properties were similar, principally affected by theirconstituents although the blueberry s matrix state changed. Maximum-freeze-concentration conditionswas found as X?s = 0.69 kg solid (kg blueberry)-1, T?g = -54.86°C and T?m = -45.45°C. In conclusion, a statediagram was developed using lyophilized fruit but it can be extrapolated to whole blueberry fruit. © 2013 Elsevier B.V.